Analysis of soil Temperatures at Waltair (MAUSAM, 1963)
An analytical study of the depth and time variations of soil temperatures at Waltair has been made, Curves showing the diurnal variation of soil temperatures at different, depths on certain representative days in different months have been presented and discussed. Several interesting features are brought out from the graphs depicting the seasonal variation of the daily temperature ranges at different depths as well as from seasonal variation of mean soil temperature in different months, Finally, emphasis is also laid on the tautoehrones of mean daily temperature for various depths of observation m different months.